If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18x + -30 = 6 Reorder the terms: -30 + -18x = 6 Solving -30 + -18x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + -18x = 6 + 30 Combine like terms: -30 + 30 = 0 0 + -18x = 6 + 30 -18x = 6 + 30 Combine like terms: 6 + 30 = 36 -18x = 36 Divide each side by '-18'. x = -2 Simplifying x = -2
| 3x+5y=29 | | 82-4x=23x+16 | | 12-7x=111-28x | | -6c+9=-4c-3 | | 6x+5=-79-8x | | 6x^2+37x-35=0 | | -2x=7x-18 | | 2x^2+15=0 | | 4(2c-3)-3(c-4)= | | 80Y^2-210Y-245=0 | | y=-2.5x+4 | | 8=z-5 | | 6x+15=21 | | 3z-14=-13 | | 3x^2-16x-1=0 | | 9(y-4)+5(y+2)=16 | | 3x+7+38=180 | | n+10-2n=-5(n+2) | | w-10=8 | | w-10=18 | | 3(x-9)-11=x+4 | | -8y=7.44 | | t^2-242=0 | | y=(4x^3)-(6x^2)-(10x)+(13) | | 8x+7.28=6x+11 | | 2x+9= | | D^2-14D+45=0 | | n+10-2n=-5n(n+2) | | 3+5(x-7)=3(x+6) | | 2x^2+16x-3=0 | | 3y-14=12y-(17+15y) | | -5m=9m+14 |